Authority and How to Attain It: Pausanias, Description of Greece and Archaeological Excavations at Olympia - Vladimir V. Mihajlović (University of Belgrade, 2019)
One of the key products of archaeological work, the clear disciplinary distinction separating it from amateur curiosity or lucrative treasure hunt, is the text. Not only it stands at the end of almost every archaeological endeavour, text in its various forms often presents the source of fieldwork: archaeological excavations are preceded by (repeated) reading of previously written landscape, either represented through old travelogues, or through recent reports from archaeological surveys. In short, fieldwork and text are dialectically linked: fieldwork practice and texts mutually intertwine, confirm and (re)shape one another. Therefore, along with “founding fathers” of the discipline, some texts may also posses authority – achieved over time, confirmed, or lost.